Application of Artificial Intelligence in Advertising & Public Relations and Emerging Ethical Issues in the Ecosystem - Nikhil Kumar Gouda, Santosh Kumar Biswal, Binish Parveen (International Journal of Advanced Science and Technology, 2020)
Advertising and Public Relations (PR) remain important elementsin the marketing communication and business activities. The application of artificial intelligence (AI), of late, in advertising and PR has changed the ecosystem of marketingof the present time. Still in its infancy, it has the potential to trigger unfathomable changes in future. The insufficiency in control and uncertainty of its impact pose some pertinent questions of business ethics. This paper reviews the present applications of AI in advertising and PR and the ethical challenges it throwsto business activities.